Independent lung ventilation with use of a double-lumen endotracheal tube for refractory hypoxemia and shock complicating severe unilateral pneumonia: A case report. (2020) - Yoshida, Minoru; Taira, Yasuhiko; Ozaki, Masayuki; Saito, Hiroki; Kurisu, Miyuki; Matsushima, Shinya; Naito, Takaki; Yoshida, Toru; Masui, Yoshihiro; Fujitani, Shigeki
Abstract: Background: The indications for independent lung ventilation (ILV) in critical care settings have not been fully clarified, especially because extracorporeal membrane oxygenation (ECMO) is being used increasingly in cases of severe respiratory failure. Case report: A 90-year-old man presented with severe unilateral pneumonia, and despite conventional mechanical ventilation management with use of a single lumen endotracheal tube and high positive endo-expiratory pressure (PEEP), oxygenation and hemodynamics deteriorated. We then performed ILV using a double-lumen endotracheal tube (DLT) and two ventilators, each set at a different respiratory mode. With continuous administration of a neuromuscular blocking agent, the ventilator for the left lung (non-affected lung) was set to pressure-controlled ventilation (PCV) mode, whereas the ventilator for the right lung (affected lung) was set to bi-level mode, 1 breath/min, and high PEEP. ILV and the high PEEP applied to the affected lung prevented hyperinflation of the non-affected lung and increased pulmonary blood perfusion on the non-affected side. Thus, ILV immediately improved oxygenation and hemodynamics by correcting ventilation/perfusion mismatch. Discussion: Although ECMO is a valid treatment option for patients with severe respiratory failure, it is highly invasive intervention. ILV performed with use of a DLT is less invasive and more useful than ECMO. Thus, ILV should be kept in mind as a treatment option, especially in cases of refractory respiratory failure and circulatory failure in which the pathophysiology of the left and right lungs differs markedly.